Clinical Outcomes of Stage 2 (Pivotal) Use of a Modified Keratoprosthesis Device (ORC-KPro) in Patients with End-stage Corneal Blindness - Rahmani, Saeed; Karimian, Farid; Hassanpour, Kiana; Jafarinasab, Mohammad-Reza; Feizi, Sepehr; Safi, Sare; Javadi, Mohammad Ali (Journal of Ophthalmic and Vision Research, 2024)
Purpose: To investigate the short-term results and performance of a modified Boston keratoprosthesis device manufactured by the Ophthalmic Research Center (ORC-KPro) in patients with end-stage corneal blindness. Methods: This prospective interventional case series was conducted on patients with corneal blindness who were candidates for KPro. The inclusion criterion comprised patients with a bestcorrected visual acuity (BCVA) of less than 20/200 in both eyes, in whom the main reason for vision loss was corneal pathology. The ORC-KPro was implanted using the method previously described for Boston KPro. Results: This study focused on 12 eyes of 12 patients with an average age of 45.9 ± 16.8 (range, 19 to 70) years. Eleven patients were male. The KPro indication was corneal blindness due to chemical burns in nine patients (75%) and failure of multiple previous corneal grafts in three patients (25%). Anatomical success was achieved in all patients. The preoperative BCVA was light perception (LP) in 10 eyes and hand motion in 1 eye. Except for one patient who was diagnosed with grade C proliferative vitreoretinopathy during the surgery, the vision of all other patients (91.6%) improved after surgery. The retroprosthetic membrane (RPM) was formed in two eyes (18.1%) after six months. Of the 12 patients, 10 (83.3%) were under treatment with two antiglaucoma medications before surgery. The intraocular pressure of three eyes (25%) was estimated to be high by tactile palpation; however, it decreased in two eyes to the acceptable range. One patient underwent retinal surgery due to total retinal detachment, and two patients (16.7%) underwent vitrectomy due to endophthalmitis. Conclusion: The current study showed that, in the short term, the use of ORC-KPro achieved favorable anatomical success in patients with corneal blindness. However, the functional success rate was limited by the low visual potential due to advanced glaucoma in most patients.